Patellofemoral pain over time: Protocol for a prospective, longitudinal study investigating physical and non-physical features - Botta, Ana Flavia Balotari [UNESP]; Waiteman, Marina Cabral [UNESP]; Ducatti, Matheus Henrique Maiolini [UNESP]; Garcia, Carmen Lúcia Gomes [UNESP]; Farinelli, Lucca André Liporoni Bego [UNESP]; Bazett-Jones, David Matthew; Briani, Ronaldo Valdir [UNESP]; Azevedo, Fábio Mícolis de [UNESP] (Frontiers, 2023)
Background: This is a protocol for a prospective longitudinal study that aims to investigate: (1) group-by-time changes over a minimum of 15 months follow-up in patellofemoral pain (PFP) symptoms, biomechanical, muscle function, pain processing, and psychological features; (2) the extent to which changes in biomechanical, muscle function, pain processing, and psychological features are associated with changes in self-reported pain, physical performance measures, self-reported function, health-related quality of life (HRQOL), and physical activity level. Methods: Individuals with PFP (n = 144) and control individuals (n = 85) without PFP were assessed at baseline. Outcomes assessed included: 3D kinematics and kinetics during single leg squat, step-down and single leg hop; maximal torque and rate of torque development of hip abductors and knee extensors/flexors; force steadiness of hip abductors and knee extensors; anterior and lateral trunk endurance; pressure pain thresholds at the center of patella and contralateral shoulder; kinesiophobia (Tampa Scale for Kinesiophobia); pain catastrophizing (Pain Catastrophizing Scale); worst self-reported pain (Visual Analogue Scale); physical performance measures (Single Leg Hop Test and Forward Step-Down Test); self-reported function (Anterior Knee Pain Scale); HRQOL (Medical Outcome Short-Form 36), and physical activity level (Baecke’s Questionnaire). Follow-up assessments will be identical to the baseline and will be performed after a minimum of 15 months. Generalized linear mixed model (GLMM) will be used to investigate group-by-time differences. Linear regression models will be used to determine the extent to which changes in biomechanical, muscle function, pain processing, and psychological features are associated with changes in self-reported pain, physical performance measures, self-reported function, HRQOL, and physical activity level. Discussion: Physical and non-physical features have been previously associated with PFP. However, the present study will be the first to investigate their integrated evolution as part of the natural history of PFP and its progression. In doing so, we will be able to determine their behavior in the long-term, as well as how they prospectively associate with each other and with clinical outcomes. Ultimately, this will provide a greater understanding of predictors of long-term outcome and possible targets for interventions.
Keywords: catastrophism; fear of movement; knee cap pain; movement analysis; pain sensitization